Clima organizacional y su incidencia en la gestión académica en la unidad educativa “Héroes del 41”, año 2019. Estrategias de mejoramiento Institucional - Cruz Zambrano, Linner Narcisa (2021)
The present investigation entitled "The organizational climate and its incidence in the academic management in the Educational Unit" Héroes del 41 ", had as general objective: To diagnose the incidence of the level of organizational climate in the academic management of the Educational Unit" Héroes del 41 ", In order to find the circumstances of the general problem found in the" Héroes del 41 "Educational Unit, the general problem being: How does the level of organizational climate affect the academic management of the" Héroes del 41 "Educational Unit, year 2019 ?. The design of this research was descriptive - explanatory - correlational, the technique used is that of the questionnaire, consisting of 4 components: curriculum design, pedagogical practices, classroom management and academic monitoring; the population made up of teachers and students of the educational unit, the sample based on the non-probabilistic method. The analysis establishes that in the studied institution there is a weak management of teamwork, that academic management has weaknesses in the decision-making process therefore, a framework of action is established that results in an improvement In the development of academic and administrative activities within the educational unit, for this it is necessary to implement some institutional improvement strategies. Keywords: Keywords: organizational climate, teamwork, academic management, educational unit, role of the teacher.